2007
DOI: 10.1111/j.1463-1318.2007.01216.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after indefinite diversion/pouch excision in ileal pouch failure patients

Abstract: Quality of life after PE or ID was no different and male sexual function was significantly better after ID. Retraction of the stoma was more common in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 36 publications
1
15
0
1
Order By: Relevance
“…However, there are only a few reports on HQoL for patients with pouch failure. 7,48 In the study by Das et al, 22 both patients with excised pouches and patients with diverted pouches showed lower scores than the UK norm in all domains of the SF-36; there was however no difference between the groups. In a study by Lepisto et al, 48 18/21 patients with pouch failure answered the SF-36 instrument and were compared with controls and with 19 persons from the Finish norm database.…”
Section: Health-related Quality Of Lifementioning
confidence: 92%
See 2 more Smart Citations
“…However, there are only a few reports on HQoL for patients with pouch failure. 7,48 In the study by Das et al, 22 both patients with excised pouches and patients with diverted pouches showed lower scores than the UK norm in all domains of the SF-36; there was however no difference between the groups. In a study by Lepisto et al, 48 18/21 patients with pouch failure answered the SF-36 instrument and were compared with controls and with 19 persons from the Finish norm database.…”
Section: Health-related Quality Of Lifementioning
confidence: 92%
“…To our knowledge, only the study by Das et al has addressed the issue. 22 Ninety-seven patients (56 women) with pouch failure were included in that study; focus was on potential differences between patients undergoing pouch excision or definitive diversion. Fifty-three patients (36 women) answered the posted questionnaires on HQoL (e.g.…”
Section: Sexual Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Letztere ist nur für die wenigen Patienten geeignet, deren Rektum relativ entzündungsfrei ist und die keine Dysplasie oder ein bestehendes Karzinom im Rektum [4] haben. Die konventionelle Proktokolektomie lässt den Patienten mit einem permanenten Ileostoma zurück [5]. Aktuell ist die RPC in der Behandlung von CU die chirurgische Methode der Wahl [6].…”
Section: Dysplasie Und Adenokarzinome Im Ileum-pouch Nach Restaurativunclassified
“…Minimal information is currently available pertaining to the relative roles of these 2 surgical options for pouch failure, and especially their influence on QOL. 12,13 One of these studies 12 only reported outcomes after LI, and both studies 12,13 suffer from the drawbacks of small numbers and short follow-up. Based on the identification of this current gap in the literature, we chose to specifically evaluate the surgical outcomes and QOL after LI for pouch failure in comparison with PE for a large number of patients with prolonged follow-up.…”
mentioning
confidence: 96%